ETHICS OF THE WORKPLACE AND VALUE-BASED LEADERSHIP: HOW TO GET EMPLOYEES TO ACT ETHICALLY - Nugraha, Andika Prasetya (LPPM Universitas Ibnu Sina, 2024)
This study aims to examine the effect of clarity of value and consistency dimensions on value-based leadership (VBL) in Karimun Regency. The research method used is a survey using questionnaires as a data collection instrument. The respondents in this study were employees of Karimun Regency who were randomly selected. The results showed that value clarity had a positive influence on VBL, although not significantly. Meanwhile, consistency has an insignificant positive influence on VBL. Suggestions that can be made to increase clarity of values and build an organizational culture conducive to implementing VBL include improving communication, education, training, performance appraisal, and examples from organizational leaders and managers. By implementing these suggestions, it is expected that the organization can create a work environment that is based on strong values and strengthens the commitment of organizational members to organizational goals.